Complexity as an Antecedent for External Collaboration in New Product Development Projects - Gheshmi, Reza; Zacro, Hugo; Marimon, Frederic (International Journal of Engineering and Technology, 2018)
This study examines how project complexity in low technology-intensive small- and medium-sized enterprises (SMEs) contribute in implementation of open innovation practices, during their new product development projects. The main focus of this paper is to investigate the critical role of complexity in the project level to identifying the compatibility of those external sources involved in NPD. The low technology-intensive sector in Spain were chosen as a target context, there were many innovative SMEs operating in these industries and because these sectors were going through significant changes. Four external knowledge sources, Universities, suppliers, customers and competitors and four open innovation practices, Community, Platform, Partnership and seller-buyer agreement, in the new product development were identified. The study shows that in SMEs, project complexity plays an important role in selecting the external source and implementation of open innovation practices. The main conclusion of the study is that the external collaboration in new product development projects is determined by different dimensions of project complexities and in projects with different type of complexity, the SMEs follow different external knowledge sources and open innovation practices. The study results imply that SMEs benefit from opening up their innovation process in the new product development projects. The firms in this study employed a blend of strategies that is more compatible with dimensions of project complexity. They collaborated actively with different external knowledge source and different modes of collaboration, when they have determination of different dimensions of project complexity. Also, the study extends understanding of the strategic use of open innovation in SMEs by demonstrating how SMEs balance the risk of project complexity built on new product development and the benefit of creating a wider capability base with partnerships.Â